Encephalitis followed by optic neuritis: a case report and review of literature - Hasan, Shariful; Basri, Hamidon; Lim, Poh Hin; Stanslas, Johnson (Professional Medical Publications, 2013)
Encephalitis has been included in the causes of optic neuritis, but post encephalitic optic neuritis has been rarely reported. Majority of the cases of optic neuritis are either idiopathic or associated with multiple sclerosis, especially in western countries. This is very important in the Asian population where the incidence and prevalence of multiple sclerosis is not as high as in the Western countries. Although post infectious optic neuritis is more common in children, it can also be found in adults and is usually seen one to three weeks after a symptomatic infective prodrome. Here, we present a case of a 48 year-old-male who developed optic neuritis following viral encephalitis. His first presentation was with severe headache of two weeks duration. Viral encephalitis was diagnosed and treated. The patient presented again three weeks later with right eye pain and other features typical of optic neuritis. Corticosteroid therapy facilitated prompt recovery. Optic neuritis is an uncommon manifestation of encephalitis. It is important that both doctors and patients remain aware of post infectious cause of optic neuritis, which would enable a timely diagnosis and treatment of this reversible cause of vision loss.